Thyroid Gene Mutations in Pregnant and Breastfeeding Women Diagnosed With Transient Congenital Hypothyroidism: Implications for the Offspring’s Health - Opazo, Maria C.; Rivera, Juan Carlos; Gonzalez, Pablo A.; Bueno, Susan M.; Kalergis, Alexis M.; Riedel, Claudia A. (Frontiers in Endocrinology, 2021)
Fetus and infants require appropriate thyroid hormone levels and iodine during pregnancy and lactation. Nature endorses the mother to supply thyroid hormones to the fetus and iodine to the lactating infant. Genetic variations on thyroid proteins that cause dyshormonogenic congenital hypothyroidism could in pregnant and breastfeeding women impair the delivery of thyroid hormones and iodine to the offspring. The review discusses maternal genetic variations in thyroid proteins that, in the context of pregnancy and/or breastfeeding, could trigger thyroid hormone deficiency or iodide transport defect that will affect the proper development of the offspring.